The new financial war. (c2013) - Safa, Waddah M. (2016)
This thesis examines the potential for conflict between domestic Lebanese political (and other) pressures and international pressures that is a direct result of globalization. This conflict is further highlighted by the nature of the topic at hand: money laundering and financing of terrorism, which have seen significant growth due to globalization. It also analyzes how the U.S. money laundering laws have impacted international anti-money laundering laws and ultimately similar laws and policies in Lebanon. It examines how the latest efforts to develop efficient strategies for anti-money laundering and combating the financing of terrorism has led to the establishment of financial intelligence units combining several diverse but unified aspects of financial systems and law enforcement. This research also provides a summarized account of Lebanon’s anti-money laundering and combating the financing of terrorism regime. Through policy and discourse analysis, it explores the behavior of the Lebanese financial system in crises showing how the Central Bank’s timely intervention in problematic situations has resulted in leveling international and domestic political pressures. The main question is: How has Lebanon sustained its leading role as one of the most important financial and banking centers in the Middle East based on its longstanding banking secrecy practices as well as complied with international standards regarding anti-money laundering and combating the financing of terrorism; it is hoped that this thesis provides an informative and plausible answer.